Efektivitas Strategi Omnichannel Toko Kado Shofia dalam Menghadapi Perubahan Perilaku Konsumen - Hendrawan, Ilham (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The effectiveness of the omnichannel strategy of Toko Kado Shofia in responding to changes in consumer behavior is a study aimed at measuring the effectiveness of using an omnichannel strategy at Toko Kado Shofia in meeting the ever-changing needs of consumers. This study will examine how the mixed sales methods used, such as physical stores, e-commerce platforms, websites, and social media, affect customer shopping experience, satisfaction levels, and business performance. This research will identify key factors that influence the success or failure of the omnichannel strategy of Toko Kado Shofia. The goal is to provide improvement recommendations so that the store can optimize their strategy amidst the increasingly complex changes in consumer behavior due to the development of digital technology. In a comprehensive manner, this research is expected to provide significant benefits in understanding how to use omnichannel strategies in the retail industry, especially in gift shops. In addition, this research can also provide practical guidance for other entrepreneurs who want to improve their business performance through omnichannel strategies. This research aims to determine the extent to which the omnichannel strategy used by Toko Kado Shofia can meet the changing desires of consumers. How the integration between physical stores, e-commerce platforms, websites, and social media affects customer shopping experiences and their satisfaction. What factors influence the success or failure of this omnichannel strategy.